Early life shocks and mental health: The long-term effect of war in Vietnam - Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper provides causal evidence on early-life exposure to war on mental health status in adulthood. Using an instrumental variable strategy, the evidence indicates that early-life exposure to bombing during the American war in Vietnam has long-term effects. A one percent increase in bombing intensity during 1965-75 increases the likelihood of severe mental distress in adulthood by 16 percentage points (or approximately 50 percent of the mean) and this result is robust to a variety of sensitivity checks. The negative effects of war are similar for both men and women. These findings add to the evidence on the enduring consequences of conflict and identify a critical area for policy intervention.
Keywords: I1; I15; H56; I31; N35; O12; 330; early-life; mental health; conflict; Vietnam